TRADISI MAGEBEG-GEBEGAN GODEL SERANGKAIAN HARI RAYA NYEPI DI DESA PAKRAMAN DHARMAJATI TUKADMUNGGA KECAMATAN BULELENGKABUPATEN BULELENG (Persepektif Pendidikan Teo-Etika) - Komang Lilik Ariani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
In this study the problem of (1) the process of the Magebeg-Godebel tradition in the series of Nyepi Day in Pakraman Dharmajati Tukadmungga village, (2) the function of the Magebeg-Godebel tradition series in the Nyepi day in Pakraman Dharmajati Village, Tukadmungga, (3) the value of the Teo-Ethics education of the Magebeg-Gebegan series of Nyepi Day in Pakraman Dharmajati Village contained in the tradition of the Magebeg-Gebegan Godel series of the Nyepi day in the village of Pakraman Dharmajati Tukadmungga. The purpose of this study is (1) to know the process of the tradition of the Godebegebebebebelebetek series of Nyepi Day in the village of Pakraman Dharmajati Tukadmungga, (2) to find out the function of the tradition of the Godebebebebebebelebebetek series in the village of Pakraman Dharmajati Tukadmungga, (3) to determine the function of the tradition of the Magebeg-Godeberebebebebetau series in the Pakraman Dharmajati Tukadmungga Village, (3) Teo-Ethics education contained in the Magebeg-Godebel tradition of a series of Nyepi days in Pakraman Dharmajati Tukadmungga Village. The theories used to analyze this problem are the Theory of Religion, Theory of Structural and the Theory of Values. The method used in collecting data is observation, interview, document study. The collected data is then analyzed using data analysis techniques with the steps of data collection, data reduction, data presentation and drawing conclusions. To increase data trust and validity obtained by researchers using the technique of Triangulation Data. Keywords: Godel's Magebeg-Gebegan Tradition, Teo-Ethics Education Values